Patient and procedural risk factors for increased postoperative pain after cesarean delivery under neuraxial anesthesia: a retrospective study. (November 2020) - Mehdiratta, J.E.; Saab, R.; Chen, Z.; Li, Y-J.; Habib, A.S.
Highlights: We investigated factors associated with greater pain after cesarean delivery. 1899 patients who underwent cesarean delivery with neuraxial anesthesia included. Chronic pain, tobacco use, and anxiety associated with higher pain scores. Also repeat cesarean, black race, public insurance, intra-operative analgesics. Accuracy of the predictive model was modest at 56%. Abstract: Background: There is significant interindividual variability in pain experienced after cesarean delivery. The goal of this study was to identify risk factors for increased postoperative pain in women undergoing cesarean delivery under neuraxial anesthesia with neuraxial morphine. Methods: A retrospective chart review was conducted (June 1, 2013 to August 25, 2015). Patients were categorized into three groups, according to the weighted area-under-the-curve (AUC) of pain scores within 48 h of surgery, as mild (weighted AUC 0–3), moderate (4–6) or severe (7–10) pain. We evaluated potential factors that could influence variability in pain, including patient demographics, comorbidities, obstetric history, and surgical details. Results: A total of 1899 patients were included in the analysis. Pain was mild in 896 patients, moderate in 895, and severe in 108 patients. In the multivariable analysis, the following factors were associated with increased pain severity: history of chronic pain (OR 4.12, 95% CI 1.15 to 14.75]), current tobacco use (2.52, 1.17 to 5.44), pre-existing anxiety (1.93, 1.21 to 3.07), receipt of intra-operative intravenous ketamine or fentanyl (1.56, 1.21 to 2.01), and repeat cesarean delivery (1.54, 1.18 to 2.02). Being of non-Black race and having private health insurance were associated with lower pain severity (OR 0.44, 95% CI 0.31 to 0.62 and 0.51, 0.39 to 0.68, respectively). The overall accuracy of the model was 56%. Conclusions: Certain patient and procedural factors were associated with higher levels of reported postoperative pain. Patients with those factors may require a more targeted analgesic strategy for post-cesarean delivery pain control.